TP6.2.3 Abnormal liver function tests: A helpful diagnostic test and a predictor of severity in acute appendicitis. (28th October 2021) - Telfah, Muwaffaq; Mason, Mathew; Hollyman, Marianne; Noble, Hamish; Mahon, David; Welbourn, Richard
Abstract: Aim: Acute appendicitis (AA) is the commonest surgical emergency worldwide. The diagnosis usually is clinical but imaging and bloods tests are helpful. The study aims to establish the role of abnormalities in liver function tests (LFTs) in the diagnosis and in predicting the severity of AA. Methods: Retrospective, observational study performed in district general hospital between June 2018 and June 2019. Patients with abdominal pain and appendicectomy (excluding children <16 years with isolated ALP rise) were categorized into two groups based on presence (Group-A) or absence (Group-B) of abnormal LFTs. Demographics data, diagnosis and severity of appendicitis, hospital stay and postoperative complications were analysed. Results: Two hundred and seventy nine patients were included: Group-A (n = 146, mean age 37.5 years, M: F 1.3/1.0) and Group-B (n = 133, mean age 29.7 years, M:F 1.0/1.8). Appendicitis occurred in 85.6% of Group-A (125/146) and in 62.4% (83/133) of Group-B with positive predictive value 85.6%. The appendix was normal in 14.4% of Group-A (21/146) and in 37.6% of Group-B (50/133) with specificity of 70%. Laparotomy was required in 6.1% in Group-A (9/146) compared to 1.5% in Group-B (2/133). Average hospital stay was 4.7 days (range: 1-21) in Group-A versus 2.7 days (range 1-14) in Group-B. Readmission rate due to a postoperative complication was 16.4% in Group-A (24/146) compared to 6% in Group-B (8/ 133). Conclusion: Deranged LFTs is an additional diagnostic tool in AA and a good predictor of its severity. This may help to decrease the negative appendicectomy rate and guide surgeon in the decision-making process.